Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1993
DOI: 10.1007/bf01552160
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of pre-operative evaluation of anterior knee laxity by dynamic X-rays and by the arthrometer KT 1000

Abstract: The comparison of bilateral dynamic X-rays in passive anterior and posterior drawer with a load of 9 kg, and the arthrometer KT 1000 measurements obtained from 100 patients before anterior cruciate ligament reconstruction, confirms the good diagnostic efficiency of the following methods: (1) radiological measurement of the anterior translation of the medial compartment, as an absolute value and especially as a differential value in relation to the opposite, uninjured knee, the normal value limits being respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 19 publications
2
49
0
1
Order By: Relevance
“…First, this review excluded non-English-language articles, which may have led to the omission of additional descriptive studies of stress techniques, accuracy and reliability data, and comparative studies not available in the English language literature. Second, this review did not Lerat [29] 100 AP Anterior drawer: the patient is supine on a table with the lower extremity supported in a special leg holder and the thigh free; the foot and ankle are fixed with a strap; the opposite limb is positioned on a stool at a lower level; a free hanging 9-kg weight is hung from the distal femur Posterior drawer: the leg support is turned 180°and moved closer to support the patient and a 9-kg weight is hung from a strap at the proximal tibia …”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…First, this review excluded non-English-language articles, which may have led to the omission of additional descriptive studies of stress techniques, accuracy and reliability data, and comparative studies not available in the English language literature. Second, this review did not Lerat [29] 100 AP Anterior drawer: the patient is supine on a table with the lower extremity supported in a special leg holder and the thigh free; the foot and ankle are fixed with a strap; the opposite limb is positioned on a stool at a lower level; a free hanging 9-kg weight is hung from the distal femur Posterior drawer: the leg support is turned 180°and moved closer to support the patient and a 9-kg weight is hung from a strap at the proximal tibia …”
Section: Discussionmentioning
confidence: 91%
“…Three of five studies comparing stress radiography with the KT-1000 or KT-2000 (MEDmetric Corporation, San Diego, CA, USA) for the diagnosis of AP instability concluded that stress radiography is superior, whereas the other two studies showed excellent but equivalent diagnostic ability [7,14,29,31,45]. For diagnosis of ACL injury, stress radiography correlated with results of the pivot shift test but not the Lachman's test [15], was equivalent to the GNRB computerized arthrometer [2], and offered greater sensitivity but similar specificity to the Rolimeter [34].…”
Section: Stress Radiography Compared With Other Diagnostic Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Normal SSD is near zero [20]. Different diagnostic thresholds have been reported in the literature ranging from SSD of 2 to 5 mm [14,17,21]. In patients with complete ACL tear, Panisset et al found average SSD to be 7.4 ± 4.3 mm and used SSD >5 mm as their diagnostic threshold using Telos stress imaging (Sn 80.9 %, sp 81.8 %) [5].…”
Section: Methods Of Quantificationmentioning
confidence: 99%
“…Reliability of posterior displacement between testers is estimated to reach an ICC of 0.91 and the measurement errors reached 2.77 mm [22]. -Lerat's method [23]: In this invasive method, a mass of 9 kg is attached to the patient's thigh above his patella to induce a posterior translation of the femur compared to the tibia. This technique seems to be reliable with an intra-tester ICC superior to 0.9 [24].…”
Section: Introductionmentioning
confidence: 99%